2021
DOI: 10.1152/physrev.00038.2020
|View full text |Cite
|
Sign up to set email alerts
|

Exercise under heat stress: thermoregulation, hydration, performance implications, and mitigation strategies

Abstract: A rise in body core temperature and loss of body water via sweating are natural consequences of prolonged exercise in the heat. This review provides a comprehensive and integrative overview of how the human body responds to exercise under heat stress and the countermeasures that can be adopted to enhance aerobic performance under such environmental conditions. The fundamental concepts and physiological processes associated with thermoregulation and fluid balance are initially described, followed by a summary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
166
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(225 citation statements)
references
References 1,009 publications
(1,353 reference statements)
2
166
1
5
Order By: Relevance
“…Sweating starts immediately after the onset of exercise, which is most likely due to various central mechanisms, including the baroreceptor reflex [8]. With heat acclimatization, sweat volume can be as high as 2-3 l/h, mainly due to lowering the temperature threshold for sweating and the redistribution of sweat secretion more peripherally [9].…”
Section: Mechanisms Of Thermoregulationmentioning
confidence: 99%
“…Sweating starts immediately after the onset of exercise, which is most likely due to various central mechanisms, including the baroreceptor reflex [8]. With heat acclimatization, sweat volume can be as high as 2-3 l/h, mainly due to lowering the temperature threshold for sweating and the redistribution of sweat secretion more peripherally [9].…”
Section: Mechanisms Of Thermoregulationmentioning
confidence: 99%
“…This combination will presumably result in the most challenging environmental conditions ever observed during the Olympic Games [1], leading to significant heat stress for athletes competing in outdoor disciplines. Hence, significant performance decrements can be expected and athletes are at increased risk for the development of heat-related illnesses [2]. That these heat stress induced consequences are not purely theoretical became clear during the 2019 IAAF World Championships in Doha, Qatar.…”
Section: Front Matter: Editorialmentioning
confidence: 99%
“…Pre-cooling and per-cooling interventions attenuate core temperature during exercise and are known to improve exercise performance in the heat [4]. And a planned hydration strategy can prevent the occurrence of dehydration and associated performance loss [2]. Outcomes of these scientific studies are translated to various practical advices for athletes and coaches.…”
Section: Front Matter: Editorialmentioning
confidence: 99%
“…A recent study of athletes competing at the 2016 UCI Road World Championships in Qatar revealed that 57% of participating athletes had a history of heat-related symptoms and 17% a history of exertional heat illness [ 14 ]. It has been demonstrated that performance levels are markedly impaired during exercise in the heat [ 15 ]. For example, the maximal aerobic capacity (i.e.…”
Section: Introductionmentioning
confidence: 99%